Investigating cloud ERP providers selection for SMEs in a multi-tenant environment - Ogunrinde, Rotimi Rowland; Jusoh, Yusmadi Yah (Enhanced Research Publications, 2014)
Enterprise Resource Planning (ERP) systems provided as a service in the cloud is offering immense assistance for the Small and Medium sized Enterprises (SMEs) with respect to cost effectiveness and affordability, to be able to compete favorably and fairly with their Large Enterprises (LE) counterparts who have the financial wherewithal to adopt the rather expensive traditional or on-premise ERP Systems. However, to be able to achieve such numerous benefits such as economies of scale, improved flexibility, reduced capital cost, improved accessibility, and so on, many service subscribers (tenants) often share the same remote physical infrastructure put in place by the cloud service providers (CSPs). This multi-tenancy concept however introduces a high level of security and privacy risks unique to cloud services, such as attacks from other consumers, who may be competitors or simply hackers, sharing the same infrastructure. Hence, it becomes a challenge for the SMEs to select a suitable CSP whose security and privacy echanisms most meet the security requirements of the organizations. We critically appraise some selected frameworks for the selection of cloud computing and, more specifically cloud ERP providers in order to be able to identify dimensions and measure of selection. We compare the frameworks based on their components, criteria for selection in the approaches and the suitability for the SMEs. We discovered that there is a link between frameworks of evaluation, ranking and selection of cloud providers. In our review, we found out that current selection methods are complementary one to another in the sense that they select providers based on different criteria and can be worked upon to suit requirements of the SMEs.